Forebrain Ischemia-Reperfusion Simulating Cardiac Arrest in Mice Induces Edema and DNA Fragmentation in the Brain - Christina H. Liu; Shuning Huang; Young R. Kim; Bruce R. Rosen; Philip K. Liu (Molecular Imaging)
Brain injury affects one-third of persons who survive after heart attack, even with restoration of spontaneous circulation by cardiopulmonary resuscitation. We studied brain injury resulting from transient bilateral carotid artery occlusion (BCAO) and reperfusion by simulating heart attack and restoration of circulation, respectively, in live C57Black6 mice. This model is known to induce neuronal death in the hippocampus, striatum, and cortex. We report the appearance of edema after transient BCAO of 60 minutes and 1 day of reperfusion. Hyperintensity in diffusion-weighted magnetic resonance imaging (MRI) was detectable in the striatum, thalamus, and cortex but not in the hippocampus. To determine whether damage to the hippocampus can be detected in live animals, we infused a T 2 susceptibility magnetic resonance contrast agent (superparamagnetic iron oxide nanoparticles [SPIONs]) that was linked to single-stranded deoxyribonucleic acid (DNA) complementary in sequence to c-fos messenger ribonucleic acid (SPION-cfos); we acquired in vivo T 2 * -weighted MRI 3 days later. SPION retention was measured as T 2 * (milliseconds) signal reduction or R 2 * value (s −1 ) elevation. We found that animals treated with 60-minute BCAO and 7-day reperfusion exhibited significantly less SPION retention in the hippocampus and cortex than sham-operated animals. These findings suggest that brain injury induced by cardiac arrest can be detected in live animals.